If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-21=2(2x+1)+3(x-3)
We move all terms to the left:
-21-(2(2x+1)+3(x-3))=0
We calculate terms in parentheses: -(2(2x+1)+3(x-3)), so:We get rid of parentheses
2(2x+1)+3(x-3)
We multiply parentheses
4x+3x+2-9
We add all the numbers together, and all the variables
7x-7
Back to the equation:
-(7x-7)
-7x+7-21=0
We add all the numbers together, and all the variables
-7x-14=0
We move all terms containing x to the left, all other terms to the right
-7x=14
x=14/-7
x=-2
| 9x-7=-7=0 | | N-20x=14 | | 4n-40=7(-2n+2)=-3 | | -6+x4=-5=4 | | -2n+14=5n-21 | | 4(6x–4)=8(3x–2) | | 4(6x–4)=8(3x–2 | | 6.5-1.5=-44-2.5x | | 6p+15=9p | | 8x+23=13x-27 | | 2(4x-7)-9=4x-4 | | 6=-5t^2 | | 6-2(x-3)=4(x-5) | | 4x-14=6x+8 | | g/2-1=1.2 | | –9h+8=–8h | | 6y+4=8y-8 | | 3n+12=6n+18 | | 3-$f=2+6(-6+2f) | | F(4)=-4x+5 | | h−4=5 | | 6-5k=-8-3k | | 5/3x+1/3=131/3+7/3x | | x-10=6x+15 | | z+19+11z-20+3z+1=180 | | 0=(100/x)+(2x) | | 4m-9=m-6 | | -16t^2+96t-50=0 | | (5x+2)/3=7 | | (5x+2)/3=7 | | n5=23.425n =223.4 | | 99.96=6.8x |